2022
DOI: 10.1007/s10811-022-02806-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the zoospore release, germination, development of gametophytes and formation of sporophytes of Ecklonia radiata

Abstract: The kelp Ecklonia radiata has become a target for controlled cultivation. However, to date there are no standardised protocols for the hatchery stage of this species that result in high rates of germination, gametophyte development and transition to sporophytes. Therefore, the objective of this study was to quantify the effect of photoperiod, light intensity, temperature, nutrient media and use of GeO2 on the key hatchery processes of germination, gametophyte development and transition to sporophytes in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…The temperature-dependent change in sex ratio has not been recorded for E. radiata before. Sex ratio was constant under temperature change in E. radiata gametophytes from New Zealand (Praeger et al, 2022), but female gametophytes have been found to grow larger than males under increased temperatures (Mabin et al, 2019). A higher proportion of females can contribute to higher fertilization (Nelson, 2005) but can also a of maladaptation (Oppliger In the kelp Lessonia nigrescens, more females survived at a higher temperature toward the warmer range edge, while the opposite was true for cooler populations (Oppliger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature-dependent change in sex ratio has not been recorded for E. radiata before. Sex ratio was constant under temperature change in E. radiata gametophytes from New Zealand (Praeger et al, 2022), but female gametophytes have been found to grow larger than males under increased temperatures (Mabin et al, 2019). A higher proportion of females can contribute to higher fertilization (Nelson, 2005) but can also a of maladaptation (Oppliger In the kelp Lessonia nigrescens, more females survived at a higher temperature toward the warmer range edge, while the opposite was true for cooler populations (Oppliger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The species could also readily contribute to the bulk ‘kelp biomass’ market targeted at fertiliser and alginate production, and perhaps as a source of nutraceuticals (e.g., fucoidan) 1,63 . The first studies targeting nursery cultivation methods for the species that underpin near and offshore cultivation are emerging 55,64,65 . Despite the extensive ecological knowledge of the species, its aquaculture potential is largely unknown.…”
Section: Priority Seaweeds For Cultivation and Knowledge Gapsmentioning
confidence: 99%
“…1,63 The first studies targeting nursery cultivation methods for the species that underpin near and offshore cultivation are emerging. 55,64,65 Despite the extensive ecological knowledge of the species, its aquaculture potential is largely unknown.…”
Section: E Radiata (Golden Kelp)mentioning
confidence: 99%
“…The female gametophytes produce oogonia that are fertilized by sperm released from antheridia on the male gametophyte and develop into the macroscopic sporophyte (Lüning & Müller, 1978; Maier et al., 2001; Wernberg, Coleman, Babcock, et al., 2018). This gametophyte development is highly dependent on factors such as temperature (Praeger et al., 2022), irradiance (Morelissen et al., 2013), photoperiod (Martins et al., 2017), and nutrients (Nielsen et al., 2016). In the field, these factors fluctuate significantly over time and space and also influence the growth and reproduction of the adult sporophyte (Fairhead & Cheshire, 2004; Hurd et al., 2014; Mabin et al., 2013; Novaczek, 1984a; Wernberg, de Bettignies, et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This broad tolerance is likely linked to its large latitudinal range (Wernberg, Coleman, Babcock, et al, 2018) even though genetic structuring of populations occurs, and genotypes have differing thermal tolerance (Alsuwaiyan et al, 2021;Nepper-Davidsen et al, 2021;Wernberg, Coleman, Bennett, et al, 2018). Optimal temperatures for gametophyte development in Tasmania are ~20°C (Mabin et al, 2013;Mohring et al, 2014), which is ~3°C higher than for gametophytes from New Zealand (Praeger et al, 2022) but lower than for gametophytes from F I G U R E 1 Schematic thermal performance curve showing key parameters: thermal optimum (T opt ) at which the performance (r) is maximal (r max ), thermal minimum (T min ), thermal maximum (T max ) where r = 0.05 × r max , and thermal breadth (T br ) the range where r ≥ 0.8 × r max . Additionally, the thermal safety margin (TSM) and warming tolerance (WT) can be estimated as the difference between T opt or T max and the in situ temperature (T hab ) respectively.…”
Section: Introductionmentioning
confidence: 99%